PEMBERDAYAAN OLAHAN PUPUK ORGANIK DEMI MENJAGA KESEIMBANGAN EKOSISTEM DI DUSUN KEDUNG LIKIT, DESA KALISAT, KECAMATAN REMBANG, KABUPATEN PASURUAN - Irianto, H. Heru Irianto; Niko, Karel (Semeru: Jurnal Pengabdian Kepada Masyarakat, 2024)
The main activity of the Heraclitus 011 grup real work lecture is providing training and practice in making organik fertilizer from livestock manure in Kedung Likit Hamlet, Kalisat Village, Rembang District, Pasuruan Regency. Organik fertilizer is a type of fertilizer that comes from natural materials that contain organik materials, such as plant, animal or other organik waste. Organik fertilizer contains essential nutrient for plants. In the Hamlet where we carry out KKN activities, farmers and local Hamlet still rely on chemical fertilizer to grow crops, where excessive use of chemical fertilizers can cause physical damage to the soil and the cost or purchasing fertilizer is also relatively expensive. Therefore, our group is implementing and educational program for making organik fertilizer using livestock manure as the basic ingredient. It is hoped that the organik fertilizer results can be applied to agricultural land to reduce the use of chemical fertilizers.